2014
DOI: 10.1016/j.ijfatigue.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Tensile fatigue behaviour of Ultra-High Performance Fibre Reinforced Concrete combined with steel rebars (R-UHPFRC)

Abstract: a b s t r a c tUltra-High Performance Fibre Reinforced Concrete (UHPFRC) combined with steel rebars, subsequently called R-UHPFRC, is a promising building material implying a novel technology for the improvement of concrete structures. Steel rebars enhance effectively the resistance of UHPFRC while reducing variability in the tensile behaviour of monolithic UHPFRC due to variation in fibre distribution and orientation. When a thin layer of R-UHPFRC is overlaid on top of a concrete bridge deck slab, it is subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 10 publications
3
21
0
2
Order By: Relevance
“…Due to the specific cementitious system of UHPC (very small water/binder ratio and relatively high SP amount), it is observed that the pozzolanic reaction of FA is significantly retarded, which causes that a very limited amount of FA can react with Ca(OH) 2 after curing for 91 days. Makita T. [76] Máca P. [77] Habel K. [78] Wang W. [79] Habel K. [80] Corinaldesi V. [81] Millard S.G. [82] S.L. Yang [14] Deeb R. [83] Yazici H. [84] Reference in this study y = 6.003x + 62.732 R 2 = 0.854 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the specific cementitious system of UHPC (very small water/binder ratio and relatively high SP amount), it is observed that the pozzolanic reaction of FA is significantly retarded, which causes that a very limited amount of FA can react with Ca(OH) 2 after curing for 91 days. Makita T. [76] Máca P. [77] Habel K. [78] Wang W. [79] Habel K. [80] Corinaldesi V. [81] Millard S.G. [82] S.L. Yang [14] Deeb R. [83] Yazici H. [84] Reference in this study y = 6.003x + 62.732 R 2 = 0.854 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11. Comparison of embedded CO 2 emission of the developed eco-friendly UHPC (EUHPC) and other UHPCs or UHPFRCs [14,[75][76][77][78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Zugspannung infolge Ermüdung bleibt deutlich unter 50 % der statischen Festigkeiten. Im Grenzzustand der Ermüdungssicherheit ist der UHFB rechnerisch im Verfestigungsbereich beansprucht, und somit wurde die Ermüdungszugspannung mit einem reduzierten Elastizitätsmodul berechnet . Der Grenzzustand der Tragsicherheit ist für die andauernde Bemessungssituation hinsichtlich des Biegetragwiderstands nicht maßgebend. Mit der gewählten Rippendicke konnte der Nachweis des Querkrafttragwiderstands ohne Einlage einer vertikalen Betonstahlbewehrung erbracht werden. Um die sehr hohen normativen Entgleisungslasten für die außergewöhnliche Bemessungssituation aufnehmen zu können, mussten die beiden äußersten Rippen des Plattenrandbereichs mit höherfestem Betonstahl einer normativen Fließgrenze von 700 MPa bewehrt werden. Zur Aufnahme der normativen Anprallkraft auf den Randträger war eine starke Betonstahlbewehrung im unteren massiven Teil erforderlich.…”
Section: Entwurf Und Projektierungunclassified
“…Tensile fatigue tests conducted by [21] on steel-reinforced UHPFRC showed that it possesses a signi cant amount of fatigue resistance. erefore, UHPFRC was considered as a fatigue-strengthening material for RC structures.…”
Section: Fatigue Resistancementioning
confidence: 99%